Prevalence and incidence of hepatitis C infection amongst men who have sex with men in a population‐based pre‐exposure prophylaxis program in British Columbia, Canada. (28th March 2022) - Thompson, Kyle A.; Blank, Gabriel; Toy, Junine; Moore, David M.; Lachowsky, Nathan; Bacani, Nicanor; Zhang, Wendy; Sereda, Paul; Lima, Viviane D.; Barrios, Rolando; Montaner, Julio S. G.; Hull, Mark W.
Abstract: Background: Men who have sex with men (MSM) are at risk for sexually‐transmitted hepatitis C (HCV). Evidence for HCV infection in the context of pre‐exposure prophylaxis (PrEP) use in North America is limited. We sought to characterize baseline HCV prevalence and incidence in MSM receiving PrEP in British Columbia (BC), Canada. Methods: We followed individuals in the BC PrEP program from January 2018 to August 2019. We evaluated baseline prevalence and incident seroconversions (newly positive HCV antibody). A multivariable logistic regression model was performed in MSM for factors associated with HCV prevalence at enrollment, including reported prior sexually transmitted infection (STI), HIV Incidence Risk Index for MSM score, PrEP use because of a partner living with HIV, and location of residence. Results: The median age of the cohort was 33 years, 98.3% male, with 3058 person years (PY) of follow‐up. Baseline HCV prevalence was 0.82% (31/3907 MSM enrollees) and HCV incidence ( n  = 3) was 0.15 per 100 PY (95% confidence interval [CI] 0.03–0.45). In multivariable analysis, initiating PrEP because of a partner living with HIV (adjusted odds ratio [aOR] 5.02; 95% CI 1.87–13.47) and prior STI (aOR 2.34; 95% CI 1.04–5.24) were associated with positive HCV status. Conclusions: Baseline HCV prevalence and incidence was low amongst MSM in a population‐based PrEP program in BC, Canada. HCV was associated with bridging from populations living with HIV and evidence of a reported prior STI as a PrEP indicator condition amongst MSM. PrEP initiation may be an opportunity for linkage to HCV screening and treatment.